Comparative assessment of mouse models for experimental orthodontic tooth movement - Christian Kirschneck (Nature Portfolio, 2020)
Abstract Animal experiments are essential for the elucidation of biological-cellular mechanisms in the context of orthodontic tooth movement (OTM). So far, however, no studies comparatively assess available mouse models regarding their suitability. OTM of first upper molars was induced in C57BL/6 mice either via an elastic band or a NiTi coil spring for three, seven or 12 days. We assessed appliance survival rate, OTM and periodontal bone loss (µCT), root resorptions, osteoclastogenesis (TRAP+ area) and local expression of OTM-related genes (RT-qPCR). Seven days after the elastic bands were inserted, 87% were still in situ, but only 27% after 12 days. Survival rate for the NiTi coil springs was 100% throughout, but 8.9% of the animals did not survive. Both methods induced significant OTM, which was highest after 12 (NiTi spring) and 7 days (band), with a corresponding increase in local gene expression of OTM-related genes and osteoclastogenesis. Periodontal bone loss and root resorptions were not induced at a relevant extent by neither of the two procedures within the experimental periods. To induce reliable OTM in mice beyond 7 days, a NiTi coil spring is the method of choice. The elastic band method is recommended only for short-term yes/no-questions regarding OTM.